2016
DOI: 10.1007/s10726-016-9494-6
|View full text |Cite
|
Sign up to set email alerts
|

A Robustness Study of State-of-the-Art Surrogate Weights for MCDM

Abstract: A vast number of methods for solving multi-criteria decision problems have been suggested for assessing criteria weights requiring more exact input data than users normally are able to provide. In particular, the selection of adequate criteria weights is difficult and in order to be realistic, other methods must be introduced. One class of such methods is to introduce so called surrogate weights, where numerical weights are assigned to each criterion based on a cardinal or ordinal rank ordering, assumed to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 22 publications
0
34
0
4
Order By: Relevance
“…ROC and RR and weights perform better when this assumption is valid (Danielson & Ekenberg, 2017). In the direct rating method, decision makers assign a weight of 100 to the attribute offering the most desired swing and lower weights to less preferable swings, but there is no constraint on what the weights sum to.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…ROC and RR and weights perform better when this assumption is valid (Danielson & Ekenberg, 2017). In the direct rating method, decision makers assign a weight of 100 to the attribute offering the most desired swing and lower weights to less preferable swings, but there is no constraint on what the weights sum to.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This assumption favors RS weights. Danielson and Ekenberg (2017) suggest the use of cardinal counterparts to RR, RS, and ROC weights in order to reflect, not only the ranks of attribute swings, but the strengths of preference between them. While these weights may be appropriate to many multiattribute decision problems, by also requiring elicitations of strength of preference, they would add to the already large number of judgments required in scenario planning-based decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While the evaluation of multiple criteria by a single decision maker is rather straightforward, the comparison of many stakeholder evaluations is far from obvious and a plethora of suggestions on how this could be done can be found in the literature (Danielson and Ekenberg 2016 ). Recent analyzes in this field suggest that cardinal ranking methods are superior in a number of ways when compared to other ranking methods (Danielson and Ekenberg 2017 ). We therefore adopt this approach for our case too.…”
Section: Multi-criteria Analysis Of Optionsmentioning
confidence: 99%
“…A review of current quantitative multi-criteria decision aid methods can be found in Danielson and Ekenberg ( 2016 ). The cardinal ranking method and its mathematical representation are discussed in detail in Danielson and Ekenberg ( 2017 ). This method was selected because it is superior to other MCA approaches in a number of ways (see again the simulation tests by Danielson and Ekenberg 2016 , 2017 ) and could be implemented within the scope of the criteria introduced above.…”
Section: Multi-criteria Analysis Of Optionsmentioning
confidence: 99%